Productivity and profit enhancement through turmeric (Curcuma longa)intercropped with okra (Abelmoschus esculentus) in Punjab - KUMAR, RAJENDER; THAKUR, MANISHA; PAL, VAJINDER (The Indian Journal of Agricultural Sciences, 2026)
Turmeric (Curcuma longa L.), a long-duration crop overlapping with the rainy (kharif) season, limits the growth period of subsequent winter (rabi) crops. To enhance income, intercropping with short-duration crops is viable due to turmeric’s slow initial growth, which leaves inter-row spaces uncovered for about four months. Therefore, an experiment was conducted during rainy (kharif) season of 2020 and 2021 at School of Organic and Natural Farming, Punjab Agricultural University (PAU), Ludhiana, Punjab to study the effects of intercropping okra (Abelmoschus esculentus L.) with turmeric on the growth, yield and profitability of primary crop and the intercropping system. The treatments, viz. Sole turmeric (30 cm × 20 cm spacing) flat planting (T1); Turmeric + okra in 2:1 flat planting (T2); Turmeric + okra in 3:1 flat planting (T3); Sole turmeric crop on 67.5 cm bed planting (T4); Turmeric + okra in 2:1 bed planting (T5); Turmeric + okra in 4:1 bed planting (T6); and Sole okra sown at 45 × 15 cm (T7) were tested under randomised block design (RBD) using three replications. The results revealed that intercropping of turmeric and okra in a 2:1 ratio, under either flat or bed planting methods, resulted in higher yields of both okra and turmeric. The experiment revealed that cultivating turmeric and okra in a 2:1 ratio on either flat or bed planting methods improved the yield, growth, and profitability of both crops. Over two years, this intercropping system achieved 300 and 304.2 q/ha equivalent fresh rhizome yield, 16.2 and 18.8% higher than sole turmeric planted, respectively under the same methods. The system also generated additional returns of ₹38,600 and ₹49,388/ha indicating the potential of okra as an intercrop to enhance productivity and profitability, especially for small farmers.